Development of a competency-based framework to standardise African traditional health knowledge and practices in nursing curriculum in South Africa. - Mulaudzi, Fhumulani Mavis (University of Pretoria, 2024)
Thesis (PhD (Nursing Science))--University of Pretoria, 2023.